Mitigação dos impactos socioambientais nos empreendimentos eólicos: o caso de Icapuí/CE. - Rangel, Kamila Louzada (2019)
The implementation of large wind farms in the Brazilian northeast has caused several negative social-environmental impacts on the physical, biological and socioeconomic environment of the territories that receive this technological intervention, which is environmentally sustainable. Under the hegemonic discourse of clean energy and diversification of the energy matrix, natural resources have been depleted and socio-environmental conflicts in traditional communities have increased due to the intervention in their social practices and their ways of life. This research analyzes the effects of the implantation of a wind complex in the city of Icapuí, Ceará, Brazil. The main objective of this research is to analyze the mitigating measures and the conditions required by the Environmental Agency in order to verify if they contribute to the minimization of the social and environmental impacts caused to the communities that suffer the direct and indirect impacts of the enterprise. Through a qualitative analysis of interviews, bibliographic and field researches it seeks to understand the perception of the directly impacted community on the conditions imposed by the environmental agency for the granting of the environmental licenses, as well as the socio-environmental impacts and the corresponding mitigation measures proposed by the Environmental Impact Study presented by the entrepreneur.